Early GSWC Clippings 1920 - (:unkn) unknown (My University, 1920)
South Georgia State Normal College has various exciting activities that it is hosting. Field Day and May Day are to name a few. Several art performances happened during this time that the girls enjoyed participating in.
Early Georgia State Women's College (G.S.W.C). " Early GSWC Clippings 1920," 1912-2000. 1 electronic record. 1 pdf document.
Keywords: Clippings (Books, Newspapers, etc.); Georgia State Woman's College; Newspapers